(3Gdehabi aj GdfMhs - (3eMeO Hf CMeO Hf EHQGgje, CHh GdMSf, GdeYQha HGHf cjSGf,J (B299 (3g` s
(3ChdgG (B:s
(3bGd CHh GdMSf CMeO Hf eMeO cjSGf (B: (3bGd di CHh MSGf WdH Gdehab TjFkG ef eNJUQGJ GdfMh aYed dg ZjQ cJGH s
(3BNQgG (B:s
(3hef bhdc (B: (3KhH NR (B: (3Ci KhH ef NR , hZdGe RjO Ci ZdGe dRjO Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B308 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B213s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(100 / 3 (3b(B) s
Keywords: (3GdfMhs